FAKTOR INDIVIDU YANG MEMPENGARUHI PERILAKU KESELAMATAN PADA PEKERJA DI BAGIAN FILLING POUCH - Ajeng Perwitasari Lestari; Indri Santiasih; Am Maisarah Disrinama (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2020)
The highest accident rate in a palm oil processing company in the filling pouch area. With a noise intensity condition of more than 85 dB, it can make the work environment one of the things that affects the high number of accidents in that area. This study aims to determine the influence of noise levels, physical workload and individual factors (age, work period, knowledge and personality) on safety behaviour and hazard control based on the control hierarchy. Taking noise level data taken from secondary data, physical workload is calculated by calculation of calorie requirements, individual factors using questionnaire based on work instructions and big five inventory questionnaire. For safety behaviour data carried out by observation 20 times. Data collected from 48 sample filling pouch operators. Data analysis uses Binary Regression Logistic. The results found age factor (p-value = 0.001), work period (p-value=0.004), conscientiousness trait (p-value=0.016) and extraversion trait (p-value=0.005) are influence safety behaviour. The recommendation are grading barriers between worker and machines, reducing the work hours, moving worker to areas with lower noise level, preparing behaviour based on safety and personality test before recruiting.